Pengembangan Adaptive Hospitality Competency Leadership Framework dalam Penguatan Competency Matrix Pimpinan Puncak Industri Akomodasi di Bali - I Gusti Agung Ngurah Darma Suyasa; Made Budiarsa; Putu Devi Rosalina (Lembaga Pengembangan Kinerja Dosen, 2026)
This applied study analyzes the relationship between leadership styles and key competency dimensions in developing a competency matrix for top executives in Bali’s accommodation industry. The study is motivated by the need for hotels, villas, resorts, and accommodation organizations to assess leadership readiness more systematically, rather than relying solely on seniority or departmental experience. A qualitative approach with an interpretive case study design was employed, supported by descriptive perception data from 58 respondents and in-depth interviews with senior leaders in the hospitality industry. Data were analyzed using thematic interpretation, descriptive synthesis, and triangulation of questionnaire responses, interviews, observations, and documentation. The findings indicate that the effectiveness of top executives does not depend on a single leadership style. Transformational leadership plays a significant role in developing behavioral and interpersonal competencies, including communication, problem-solving, change management, openness to new ideas, and team innovation. Meanwhile, transactional leadership remains essential for achieving organizational targets, profitability, operational control, and service standardization. The highest-rated competency dimension was behavioral and interpersonal competency (4.88), followed by core competency (4.81), managerial and leadership competency (4.73), and technical or functional competency (4.67). The novelty of this study lies in the development of the Adaptive Hospitality Competency Leadership Framework, an integrative model that connects leadership styles, competency development, matrix structure coordination, and organizational performance improvement within accommodation organizations.